Corporate Strategy And Non-Financial Performance Of Deposit Money Banks In Abeokuta And Ijebu-Ode, Ogun State, Nigeria: Array - Sule, Olatunji Eniola; Amah, Edwinah (The Journal of Accounting and Management, 2021)
This study investigated the relationship between corporate strategy and non-financial performance of deposit money banks in Ogun State. A quantitative, cross-sectional survey research design was adopted. The population consisted of the non-managerial staff of deposit money banks in Abeokuta and Ijebu-Ode branches. Probability simple random sampling was adopted to select respondents. A sample size of 152 respondents were obtained and used for analysis purposes. Pearson Product Moment Correlation was used to measure the correlation between variables. The findings revealed that there is evidence of a relationship between corporate strategy and non-financial performance of deposit money banks in Ogun State. It is recommended that the deposit money banks should improve their customer intimacy, product leadership and disruptive innovation strategies to sustain the loyalty of their customers and reduce staff turnover intentions.